Inside Solid State Drives (SSDs) - Micheloni, Rino.; Marelli, Alessia; Eshghi, Kam.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Solid State Drives (SSDs) are gaining momentum in enterprise and client applications, replacing Hard Disk Drives (HDDs) by offering higher performance and lower power. In the enterprise, developers of data center server and storage systems have seen CPU performance growing exponentially for the past two decades, while HDD performance has improved linearly for the same period. Additionally, multi-core CPU designs and virtualization have increased randomness of storage I/Os. These trends have shifted performance bottlenecks to enterprise storage systems. Business critical applications such as online transaction processing, financial data processing and database mining are increasingly limited by storage performance. In client applications, small mobile platforms are leaving little room for batteries while demanding long life out of them. Therefore, reducing both idle and active power consumption has become critical. Additionally, client storage systems are in need of significant performance improvement as well as supporting small robust form factors. Ultimately, client systems are optimizing for best performance/power ratio as well as performance/cost ratio. SSDs promise to address both enterprise and client storage requirements by drastically improving performance while at the same time reducing power. Inside Solid State Drives walks the reader through all the main topics related to SSDs: from NAND Flash to memory controller (hardware and software), from I/O interfaces (PCIe/SAS/SATA) to reliability, from errror correction codes (BCH and LDPC) to encryption, from Flash signal processing to hybrid storage. We hope you enjoy this tour inside Solid State Drives.
Preface -- Foreword -- Acknowledgements -- About the editors -- 1. SSD market overview -- 2. SSD Architecture and PCI Express interface -- 3. SAS and SATA SSDs -- 4. Hybrid storage -- 5. NAND Flash technology -- 6. NAND Flash design -- 7. NAND & Controller co-design for SSDs -- 8. SSD reliability -- 9. Efficient wear leveling in NAND Flash memory -- 10. BCH for Solid-State-Drives -- 11. Low-Density Parity-Check (LDPC) codes -- 12. Protecting SSD data against attacks -- 13. Flash Signal Processing and NAND/ReRAM SSD -- Index.-.
Keywords: Physics; Computer hardware; Systems engineering; Physics; Solid State Physics; Circuits and Systems; Computer Hardware